PERBANDINGAN HASIL BELAJAR IPS TERPADU ANTARA MEDIA AUDIO-VISUAL DENGAN MEDIA GRAFIS - Lusiana Simamora; Pargito Pargito; Sudarmi Sudarmi (JPG (Jurnal Penelitian Geografi), 2015)
This study aimed to analyze the differences in the average value of Integrated Social Science learning outcomes before subjected to audio-visual media with graphic media, the differences in the average value of Integrated Social Science learning outcomes after subjected to audio-visual media with graphic media, the differences in gain values of Integrated Social Science learning outcomes who are taught using audio-visual media and graphic media. The research used a quasi-experimental method. The population were all students of class VII which consists of two classes such as experimental class and a control class. Data analysis was performed by t test. The results were there is no difference in the average value of Integrated Social Science learning outcomes before subjected to audio-visual media with graphic media, there are differences in the average value of Integrated Social Science learning outcomes after subjected audio-visual media with graphic media, there are differences in gain values of Integrated Social Science learning outcomes who are taught using audio-visual media and graphic media.Penelitian ini bertujuan untuk menganalisis perbedaan nilai rerata hasil belajar IPS Terpadu sebelum dikenai media audio-visual dengan media grafis,perbedaan nilai rerata hasil belajar IPS Terpadu sesudah dikenai media audio-visual dengan media grafis,perbedaan nilai gain hasil belajar IPS Terpadu yang diajarkan menggunakan media audio-visual dan media grafis. Penelitian menggunakan metode eksperimen semu. Populasi dalam penelitian ini adalah seluruh siswa kelas VII yang terdiri dari dua kelas yaitu kelas eksperimen dan kelas kontrol. Analisis data dilakukan dengan uji t. Hasil penelitian menunjukkan bahwa tidak ada perbedaan nilai rerata hasil belajar IPS Terpadu sebelum dikenai media audio-visual dengan media grafis,ada perbedaan nilai rerata hasil belajar IPS Terpadu sesudah dikenai media audio-visual dengan media grafis,ada perbedaan nilai gain hasil belajar IPS Terpadu yang diajarkan menggunakan media audio-visual dan media grafis.Kata kunci: audio-visual, grafis, hasil belajar